Protection of People at Sea under International Law: Lesson Learnt from Pushback Action to boat people in Indonesia and Malaysia - Puspitawati, Dhiana; Susanto, Fransiska Ayulistya (Brawijaya Law Journal, 2023)
People at sea, one of which is the Boat People, has become a problem not only for Europeans but also in Southeast Asia with increasing asylum seekers from Rohingya and migrants from Bangladesh. Southeast Asia is already facing the problem of boat people returning from the Vietnam Asylum. However, an old story becomes a new story that never ends in Southeast Asia when the strategist state to Sanctuary did not participate in the 1951 Geneva Convention. As a result, many people faced pushback and died or lost at sea. This research will discuss the extent to which “protection of persons at sea” and the “search and rescue” can cover the protection of boat people under UNCLOS 1982. This study also analyses how UNCLOS 1982 will work to protect boat people when states protect themselves with the "non-party Geneva Convention 1951". Researchers argued that protection for people at sea, and the  of search and rescue cover all dangerous situations faced by all people at sea, even if they are asylum seekers or boat people. They must first be protected from danger at sea, brought ashore, and the territorial state can exercise judgment on them. The "non-state party" has become a shield for Indonesia, and Malaysia to reject boat people and even push boat people back from their territory. However, the two countries are part of the UNCLOS 1982 with the obligation to carry out search, rescue, and protect humans at sea. As a result, they must rescue them and bring them ashore first before they are deported or pushed back from their boats. To investigate the relationship between the protected “protection of persons at sea” and the “search and rescue” and boat people, this paper seeks to assess UNCLOS 1982, customary international law and related cases.